Evaluation of bond strength and thickness of adhesive layer according to the techniques of applying adhesives in composite resin restorations - Hueb de Menezes, Fernando Carlos; Silva, Stella Borges da; Valentino, Thiago Assuncao; Hueb de Menezes Oliveira, Maria Angelica; Souza Rastelli, Alessandra Nara de [UNESP]; Concalves, Luciano de Souza (Quintessence Publishing Co Inc, 2013)
Adhesive restorations have increasingly been used in dentistry, and the adhesive system application technique may determine the success of the restorative procedure. The aim of this study was to evaluate the influence of the application technique of two adhesive systems (Clearfil SE Bond and Adper Scotchbond MultiPurpose) on the bond strength and adhesive layer of composite resin restorations. Eight human third molars were selected and prepared with Class I occlusal cavities. The teeth were restored with composite using various application techniques for both adhesives, according to the following groups (n = 10): group 1 (control), systems were applied and adhesive was immediately light activated for 20 seconds without removing excesses; group 2, excess adhesive was removed with a gentle jet of air for 5 seconds; group 3, excess was removed with a dry microbrush-type device; and group 4, a gentle jet of air was applied after the microbrush and then light activation was performed. After this, the teeth were submitted to microtensile testing. For the two systems tested, no statistical differences were observed between groups 1 and 2. Groups 3 and 4 presented higher bond strength values compared with the other studied groups, allowing the conclusion that excess adhesive removal with a dry micro-brush could improve bond strength in composite restorations. Predominance of adhesive fracture and thicker adhesive layer were observed via scanning electron microscopy (SEM) in groups 1 and 2. For groups 3 and 4, a mixed failure pattern and thinner adhesive layer were verified. Clinicians should be aware that excess adhesive may negatively affect bond strength, whereas a thin, uniform adhesive layer appears to be favorable. (Quintessence Int 2013;44:9-15)
Keywords: adhesive system; bond strength; composite resin